Impact of event scale–revised: A new analysis of its factor structure as applied to two Portuguese samples during the COVID-19 pandemic - Figueiredo, Paulo (2024)
This study used the Portuguese version of the Impact of Event Scale-Revised (IES-R) to assess the risk of psychological disturbances associated with the COVID-19 pandemic in two independent samples of the Portuguese population. The psychometric characteristics of the scale were also assessed. Data was collected through an online survey and its internal consistency was examined. The internal consistency of the scale was high. Factor analysis found different dimensional structures for the scale in the two samples: a three-factor in the first sample and a four-factor structure in the second sample. The different factor structures confirmed the dependence of the results on the characteristics of the samples and the situation where it is applied. Despite these differences in structure, this study showed that the Portuguese version of the IES-R is a reliable tool to measure psychological distress associated with traumatic events such as the COVID-19 pandemic.